Ethyl 2-hydroxy-5,11-dioxopyrrolo[2,1-c][1,4]benzodiazepine-10-acetate - Ourahou, S.; Chammache, M.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(16)H(18)N(2)O(5), consists of a benzodiazepinedione system fused to a pyrrole system. The seven-membered ring adopts a boat-shaped conformation (with the methine C atom as the prow); the five-membered ring adopts an enveloped-shaped conformation (with the hydroxy-bearing C atom as the flap). The hydroxy group is hydrogen bonded to the carbonyl O atom of an adjacent molecule generating a zigzag chain in the crystal structure.